Comparative Evaluation of Shear Bond Strength of Three Different Luting Cements toward Ceramic and Dentin for All Ceramic Restorations: An in vitro Study - Zareen, S Ayesha; Usman, Jafar Abdulla Mohamed; Haribabu, R (Journal of Orofacial Research, 2013)
All ceramic restorations benefit from resin cement bonding to the tooth. No currently available luting agent is ideal for all situations. The comparison of the bonding ability of differentluting cements to ceramic and dentin is thus deemed necessary. The purpose of this study was to evaluate the shear bond strength of different luting cements to both ceramic and dentinand then to evaluate the mode of bond failure by scanning electron microscopy.